The The Relationship of Self Efficacy of Fluid Control and Interdialytic Weight Gain (IDWG) at Hemodialysis Unit, Panti Rapih Hospital, Yogyakarta - MARIA DHITA SURYANI LUMBAN GAOL (Caring : Jurnal Keperawatan, 2021)
Hubungan Self Efficacy Pengendalian Cairan dengan Interdialytic Weight Gain di Unit Hemodialisa Rumah Sakit Panti Rapih Yogyakarta Maria Dhita Suryani Lumban Gaol1a, Theresia Tatik Pujiastuti1b, Yulia Wardani1c 1 Program Studi Ilmu Keperawatan STIKes Panti Rapih Yogyakarta a dhitakrista@gmail.com b thtatikpujiastuti@gmail.com c danygirlspu@gmail.com The Relationship of Self Efficacy of Fluid Control and Interdialytic Weight Gain (IDWG) at Hemodialysis Unit, Panti Rapih Hospital, Yogyakarta Abstract The changes of fast-paced and practical lifestyles lead people to unhealthy lifestyles such as consuming instant foods and drinks, lack of activities, and lack of health information. This situation results an increasing numbers of non-communicable diseases, including Chronic Kidney Disease (CKD). Stage 5 CKD requires hemodialysis as renal replacement therapy. One of the problems on hemodialysis patients is an increasing Interdialytic Weight Gain (IDWG) which can cause various complications. Therefore, the IDWG of hemodialysis patients must be controlled by performing fluid control which is highly supported by self-efficacy. The objective of this study is to determine the relationship between fluid control self-efficacy and IDWG at the Hemodialysis Unit, Panti Rapih Hospital, Yogyakarta. This study was conducted by using a cross sectional quantitative method. The total sample of 169 respondents were taken by accidental sampling of 292 patients who underwent hemodialysis. Data analysis was conducted by univariate and bivariate using the Spearman Correlation Test. As the results, the study found that the characteristics of respondents are predominantly based on the age range of 45-64 years (54.4%), male (58.6%), college/ university graduated (46.7%), the length of undergoing hemodialysis was less than 2 years (50.9%), has comorbid (71.6%), has a hypertension’s comorbid (44.1%), IDWG ? 3% or severe (58.6%), high fluid control self-efficacy (98.2%) . Statistically there is no significant relationship between self-efficacy of fluid control and IDWG with a p value of 0.776 (> 0.05). Thus it can be concluded that there is no significant relationship between self-efficacy of fluid control and IDWG. Based on the results of the study, the further research on other factors that influence IDWG such as fluid intake, knowledge and compliance with fluid control in patients undergoing hemodialysis are suggested. Patients who undergo hemodialysis are advised to restrict fluids so that the IDWG value does not exceed the tolerance value, namely ?3%. Keywords: Hemodialysis, fluid control, self efficacy, interdialytic weight gain Abstrak Perubahan gaya hidup serba cepat dan praktis menggiring masyarakat saat ini pada pola hidup tidak sehat seperti mengkonsumsi makanan minuman instan, kurang beraktivitas, dan minim informasi kesehatan. Keadaan ini berakibat meningkatnya kejadian penyakit tidak menular, salah satunya gagal ginjal kronis. Gagal ginjal kronis stage 5 membutuhkan hemodialisa sebagai terapi pengganti ginjal. Salah satu masalah pasien hemodialisa adalah peningkatan interdialytic weight gain (IDWG) yang dapat menyebabkan berbagai komplikasi. Oleh karena itu IDWG pasien hemodialisa harus dikendalikan dengan melakukan pengendalian cairan yang sangat didukung oleh self efficacy. Penelitian ini bertujuan mengetahui hubungan self efficacy pengendalian cairan dengan IDWG di Unit Hemodialisa Rumah Sakit Panti Rapih Yogyakarta. Penelitian ini menggunakan metode kuantitatif cross sectional. Jumlah sample 169 responden dari total 292 pasien yang menjalani hemodialisa, diambil secara accidental sampling. Analisa data dilakukan secara univariat dan bivariat menggunakan Uji Korelasi Spearman. Hasil penelitian didapatkan data karakteristik responden berdasarkan usia terbanyak pada rentang usia 45-64 tahun (54,4%), jenis kelamin laki-laki (58,6%), perguruan tinggi (46,7%), lamanya menjalani hemodialisa kurang dari 2 tahun (50,9%), memiliki komorbid (71,6%), komorbid hipertensi (44,1%), IDWG ? 3% atau berat (58,6%), self efficacy pengendalian cairan tinggi (98,2%). Secara statistik tidak terdapat hubungan yang signifikan antara self efficacy pengendalian cairan dan IDWG dengan p value 0,776 (>0,05). Dengan demikian disimpulkan bahwa tidak terdapat hubungan yang signifikan antara self efficacy pengendalian cairan dan IDWG. Berdasarkan hasil penelitian disarankan penelitian lebih lanjut mengenai faktor lain yang mempengaruhi IDWG selain self efficacy seperti asupan cairan, pengetahuan dan kepatuhan pengendalian cairan pada pasien yang menjalani hemodialisa. Bagi pasien yang menjalani hemodialisa disarankan melakukan pembatasan cairan agar nilai IDWG tidak melebihi nilai toleransi yaitu ?3%. Kata kunci : Hemodialisa, pengendalian cairan, self efficacy, interdialytic weight gain